Abnormal gelation phenomenon of Class G oil well cement incorporating polycarboxylic additives and its countermeasures. (15th September 2017) - Chen, Di; Guo, Jintang; Xia, Xiujian; Yu, Yongjin; Jin, Jianzhou; Xu, Ming; Liu, Shuoqiong; Feng, Yakai
Highlights: Flash-setting or flocculation for carboxylic polymer modified cement happens around 120 °C. Cross-linking for polycarboxylic cement hydrates is the main reason of the abnormal gelation. Viscosity uprush of polymer solution occurred around 120 °C accelerates the abnormal gelation of slurry. Optimization of polycarboxylic structure and addition of special salts could eliminate the abnormal gelation phenomenon. Abstract: Cementing security is endangered by the abnormal gelation phenomenon of cement slurry incorporating polycarboxylic additives occurred around 120 °C. The differences between gelatinous and non-gelatinous sections were investigated through various techniques. The polymer structural change around 120 °C could explain the abnormal gelation phenomenon by viscosity-temperature characterization. The other reasons are the polycarboxylic additives combine with Ca 2+, SiO4 2− and aluminate hydrate by cross-linking reaction. The cross-linking structure developed flocs which was embedded in calcium silicate hydrate (C–S–H) gel and intertwined around stirring shaft. The practicable methods were proposed to relieve or solve the abnormal phenomenon of cement slurry.